Surface contact behavior of an arbitrarily oriented graded substrate with a spatially varying friction coefficient. (February 2019) - Peng, Juan; Wang, Zhengjin; Chen, Peijian; Gao, Feng; Chen, Zhitong; Yang, Yugui
Highlights: A new frictional contact model of an arbitrarily oriented substrate loaded by a rigid flat indenter is investigated in the paper, in which a spatially varying friction coefficient is included. The proposed model functions effectively to explore the contact stress field as well as stress singularity near contact ends. The contact behavior is significantly influenced by the friction coefficient, inhomogeneity parameter as well as gradient orientation angle of the graded substrate. Abstract: A new frictional contact model of an arbitrarily oriented substrate loaded by a rigid flat indenter is proposed in the present paper, in which a spatially varying friction coefficient is considered. With the aid of Fourier integral transformation, the governing equation is obtained and solved semi-analytically. The surface contact stress field, the moment applied to make the indenter move vertically to the substrate's top surface, as well as the nominal friction coefficient are investigated comprehensively. It is found that the contact behavior can be well improved by choosing proper friction coefficient, inhomogeneity parameter as well as gradient orientation angle. The new finding of the present paper should be helpful to access the surface wear resistance and design various inhomogeneous composites. Graphical abstract: